Penegakan Hukum Kepolisian dalam Pengungkapan Tindak Pidana Narkotika dengan Teknik Undercover Buy (Polres Kolaka Utara) - Irabiah; Muhammad As Ari Arief Mamba; Riezka Eka Mayasari; Muhammad Ali Alala Mafing; Yahyanto; Akhmad Junaedy (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
This study aims to determine Police Law Enforcement in Disclosing Narcotics Crimes Using the Undercover Buy Technique at North Kolaka Police Station. The formulation of the problem posed is: What are the legal strengths and consequences for undercover buys made by non-Police members (informants)? and What are the obstacle factors in uncovering narcotics crimes with the Undercover Buy Technique?. The type of research used by the author in the preparation of this thesis final project is research that uses empirical research methods. The empirical legal research method is a legal research method that functions to see the law in a real sense and research how the law works in society. Covert Purchase as stipulated in Law No. 22 of 1997 which has been changed to Law No. 35 of 2009 is an addition to the investigator's authority in efforts to eradicate narcotics trafficking. This is because narcotics crimes are organized, secret crimes, and in practice they use sophisticated modus operandi and technology, making it difficult to collect evidence. Unlike other criminal acts, the implementation of covert purchases in narcotics crimes is not contrary to human rights if carried out in accordance with applicable regulations. However, it will be different if it is not implemented in accordance with applicable regulations. This is because the implementation of covert purchases cannot be separated from the participation of the community, so that the rights of the people who participate must be protected. In order to reduce errors and the implementation of covert purchases, it is necessary to know and understand clearly by investigators regarding the implementation of covert purchases themselves as stipulated in Law No. 35 of 2009. Keywords: Law Enforcement, Narcotics, Undercover Buy